Al-Rusafi and his linguistic views in his books (Journal of the College of Basic Education, 2022)
We must take a quick look to show the state of the Arabic language in that era, as the Ottoman era was dominated by delay, stagnation, and closure due to the isolation of its people from the outside and cultural world, and the “classical Arabic language” was weakened in various fields and forums, because the Turks tried as hard as they could to eliminate every trace of Arabism and anti-Arabism. Its tongue and manners, especially in the last days of this role, when some of its leaders tried to Turkify the Arab nation, by making the Turkish language the official language of the state and the language of education in schools. Until a time came, and there was no one who could read and write.” ( ).